THE EXISTING INVESTMENT ENVIRONMENT IN THE CONSTRUCTION SECTOR OF THE REPUBLIC OF UZBEKISTAN - Usmonova, Vasila; Esanov, Hayit (Science technology&Digital finance, 2023)
This article provides analytical information on the reforms carried out in the field of investments in the Republic of Uzbekistan, foreign, direct investments involved in the fields, as well as analytical information on investments involved in the construction sector, as well as author's proposals.